STS Discussion Group Meeting- ALA New Orleanss - Marilyn Von Seggern (Issues in Science and Technology Librarianship)
The STS Discussion Group will meet on Sunday, June 30 from 2-3:30 pm at the Georgia World Congress Center, Rm 307E, during the ALA Annual Conference in New Orleans. The topic will be, "Access to Science Journals: After We Cancel What Do We Do?", with discussion leaders Ron Acke, Faxon, and Lynn Hamilton, Institute for Scientific Information. The discussion will be followed by the Forum for Science and Technology Library Research in the same room. Please plan to attend!